Aging workforce: a challenge for Malaysia / Anisah Abas @ Hamdan, Aliza Abu Hassim and Fadilah Puteh - Abas @ Hamdan, Anisah; Abu Hassim, Aliza; Puteh, Fadilah (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
The world is moving towards an aging population as projected by the United Nations (UN) in the 2015 report. The number of elderly population is envisaged to increase to 1.4 billion in 2030 and 2.1 billion by 2050. Modern lifestyles and declining fertility rates have changed the demographic trends across the globe. In most countries, the trend has led to changes in the economic environment, creating unique and unprecedented challenges and opportunities for businesses. Understanding the demographic changes that are likely to unfold over the coming years as well as the challenges and opportunities they pose is crucial for achieving a sustainable development. One of the most significant issues faced by organizations and governments, especially in the developing countries, is an aging workforce. Scholars are beginning to look at the impact of an aging population across disciplines. This paper presents a meta-analysis and literature review by scholars on aging workforce challenges at the workplace. It is hoped that the paper provides an overview and better understanding of the issues to be addressed at both the organizational and national level in the Malaysian context.